Hydrogen Gas Production by an Ectothiorhodospira vacuolata Strain - Chadwick, Laurie J. (1991)
A hydrogen gas (H(2))-producing strain of Ectothiorhodospira vacuolata isolated from Soap Lake, Washington, possessed nitrogenase activity. Increasing evolution of H(2) with decreasing ammonium chloride concentrations provided evidence that nitrogenase was the catalyst in gas production. Cells were grown in a mineral medium plus 0.2% acetate with sodium sulfide as an electron donor. Factors increasing H(2) production included addition of reduced carbon compounds such as propionate and succinate, increased reducing power by increasing sodium sulfide concentrations, and increased energy charge (ATP) by increasing light intensity.